2021
DOI: 10.2478/eces-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Technology and Eco-Innovation for Green Sustainable Growth

Abstract: The world has developed to the point where productive activities are no longer only about profit and efficiency. With the rapid development of eco-technology across the world, the demand for eco-technology is growing rapidly and the question of how to protect the environment in production activities has been a popular topic for researchers in various countries. It was an inspiration for Professor Witold Wacławek (1938Wacławek ( -2020 to found in 1992 a Central European Conference ECOpole and in 1994 the journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Pampana et al [19] also found that reducing nitrogen fertiliser application did not significantly affect the nitrogen content of fruits, and the phosphorus content of fruits treated with N2 was the highest, which was 0.77 g/kg. Previous studies have found that the content of Ca and Mg in apples is related to the quality and storability of apples which has also been verified in this experiment [20,21].…”
Section: Analysis Of Resultssupporting
confidence: 86%
“…Pampana et al [19] also found that reducing nitrogen fertiliser application did not significantly affect the nitrogen content of fruits, and the phosphorus content of fruits treated with N2 was the highest, which was 0.77 g/kg. Previous studies have found that the content of Ca and Mg in apples is related to the quality and storability of apples which has also been verified in this experiment [20,21].…”
Section: Analysis Of Resultssupporting
confidence: 86%
“…In China, the government controls key resources needed by firms to develop. As the provider of resources, local governments provide relevant resources to local firm through government intervention [16][17][18]. As mentioned above, under institutional pressure, individuals tend to follow norms, while firms under pressure will follow government directives in order to gain "legitimacy" [19,20].…”
Section: Moderation Effect Of Political Statusmentioning
confidence: 99%
“…The most innovative companies are also the ones more engaged in environmental sustainability, looking for satisfying economic restrictions established by the competitive environment and the institutional pressures from all the stakeholders. Sustainability in the context of innovation can be seen in the development of innovative green products (Wu et al, 2021). Green product innovation is a fundamental factor for achieving environmental sustainability, growth, and better quality of life (Angelo et al, 2012;Zhan, Tan, Ji, & Tseng, 2018).…”
Section: The Relationship Between Innovation and Ecological Sustainab...mentioning
confidence: 99%